Independent Component Analysis for Magnetic Resonance Image Analysis. (2008) - Ouyang Ouyang, Yen-Chieh Yen-Chieh; Chen Chen, Hsian-Min Hsian-Min; Chai Chai, Jyh-Wen Jyh-Wen; Chen Chen, Cheng-Chieh Cheng-Chieh; Chen Chen, Clayton Chi-Chang Clayton Chi-Chang; Poon Poon, Sek-Kwong Sek-Kwong; Yang Yang, Ching-Wen Ching-Wen; Lee Lee, San-Kan San-Kan
Abstract : Independent component analysis (ICA) has recently received considerable interest in applications of magnetic resonance (MR) image analysis. However, unlike its applications to functional magnetic resonance imaging (fMRI) where the number of data samples is greater than the number of signal sources to be separated, a dilemma encountered in MR image analysis is that the number of MR images is usually less than the number of signal sources to be blindly separated. As a result, at least two or more brain tissue substances are forced into a single independent component (IC) in which none of these brain tissue substances can be discriminated from another. In addition, since the ICA is generally initialized by random initial conditions, the final generated ICs are different. In order to resolve this issue, this paper presents an approach which implements the over-complete ICA in conjunction with spatial domain-based classification so as to achieve better classification in each of ICA-demixed ICs. In order to demonstrate the proposed over-complete ICA, (OC-ICA) experiments are conducted for performance analysis and evaluation. Results show that the OC-ICA implemented with classification can be very effective, provided the training samples are judiciously selected.